Considering the Gender Perspective for the Concept of Smart Housing - Sharma, Aman; Mehrotra, Surabhi (Calibrating Urban Livability in the Global South, 2024)
In the realm of smart housing, the convergence of gender inclusivity and technological advancements demands wide-scale research work. This study examines gender-based participation in shaping indicators for smart housing targeting the Indian context. With a focus on home automation, energy efficiency, security, service management, and resource management, the research unveils distinct contributions from diverse genders. Utilizing a robust survey analysis methodology, the study indicates the gendered preferences and priorities across regions and genders, shedding light on the dynamics influencing attitudes towards smart housing hence, comparing two cities: Agra and Bhopal. Security and monitoring take precedence in Agra, securing 36.68% of votes, while Bhopal emphasizes energy efficiency with a leading 40%. Delving deeper into gender-specific perspectives within each city, the findings reveal the multifaceted priorities of residents. In the end, a comprehensive list of indicators for gender-inclusive smart housing is formed. Recommendations in the discussion section aim to empower policymakers and planners with practical insights. Focusing on solutions towards equitable and responsive futures, resonating with the diverse needs across genders in India.